Childhood traumatic experiences and the association with marijuana and cocaine use in adolescence through adulthood. (4th August 2017) - Scheidell, Joy D.; Quinn, Kelly; McGorray, Susan P.; Frueh, B. Christopher; Beharie, Nisha N.; Cottler, Linda B.; Khan, Maria R.
Abstract: Background and aims: Examination of longitudinal relationships between childhood traumatic experiences and drug use across the life‐course at the national level, with control of confounding by other forms of trauma, is needed. We aimed to estimate the prevalence of nine typologies of childhood traumas and the cumulative number experienced, correlation between traumas and associations between individual and cumulative number of traumas with drug use during adolescence, emerging adulthood and adulthood. Design: Secondary data analysis using the National Longitudinal Study of Adolescent to Adult Health. Setting: United States. Participants: A nationally representative sample of individuals in grades 7–12 (aged 11–21 years) during 1994–95, who were re‐interviewed during emerging adulthood (2001–02; aged 18–28) and adulthood (2007–08; aged 24–34). The analytical sample comprised 12 288 participants with data at all three waves. Measurements: Nine typologies of childhood traumas: neglect; emotional, physical and sexual abuse; parental incarceration and binge drinking; and witnessing, being threatened with and experiencing violence. Indicators of each were summed to measure cumulative dose. Outcomes were marijuana and cocaine use during adolescence, emerging adulthood and adulthood. Findings: Approximately half experienced at least one childhood trauma; traumas were not highly correlated. We observed a dose–response relationship between the number of traumas and drug use in adolescence [marijuana, adjusted odds ratio (aOR) one trauma versus none = 1.65, 95% confidence interval (CI) = 1.42, 1.92; two traumas = 2.58, 95% CI = 2.17, 3.06; ≥ four traumas = 6.92, 95% CI = 5.17, 9.26; cocaine, aOR one trauma = 1.87, 95% CI = 1.23, 2.84; two traumas = 2.80, 95% CI = 1.74, 4.51; ≥ four traumas = 9.54, 95% CI = 5.93, 15.38]. Similar dose–response relationships with drug use were observed in emerging adulthood and adulthood. Each individual trauma was associated independently with either marijuana or cocaine use in adolescence, emerging adulthood and/or adulthood. Conclusions: Childhood trauma is prevalent in the United States, and individual types as well as the total number experienced are associated significantly with marijuana and cocaine use throughout the life‐course.